The di‐peptide Trp‐His activates AMP‐activated protein kinase and enhances glucose uptake independently of insulin in L6 myotubes. Issue 1 (22nd October 2014) - Soga, Minoru; Ohashi, Ayaka; Taniguchi, Megumi; Matsui, Toshiro; Tsuda, Takanori
Abstract : These findings indicate that (1) WH activates AMPK and insulin independently enhances glucose uptake following translocation of Glut4 to the plasma membrane, (2) activation of AMPKα by WH is mediated by the LKB1 pathway, without altering the Ca 2+ ‐dependent pathway, and (3) L6 myotubes express only one type of peptide transporter (PHT1; SLC15a4), which incorporates WH into cells to activate AMPKα. Abstract : WH activates AMPK, and enhances glucose uptake in L6 myotubes independently of insulin. WH induces ATP depletion and LKB1 phosphorylates AMPK. Activation of AMPK by WH is not due to Ca 2+ dependent pathway. L6 myotubes have only one type of peptide transporter (PHT1; SLC15a4). WH activates AMPK via incorporation into cells from PHT1.